CARBON PASTE ELECTRODE MODIFIED WITH FE3O4 AND MOLECULARLY IMPRINTED POLYGLYCINE FOR VOLTAMMETRIC DETERMINATION OF RHODAMINE B - Dhiyaa Rofa, Dzikra
Rhodamine B is a synthetic dye widely used in the textile and paper industries. Rhodamin B has a carcinogenic effect, so its use in food has been banned in several countries, including Indonesia. Even so, Rhodamine B is still widely abused as a food coloring. Therefore, an analytical method is needed that can be used to determine Rhodamine B quickly and sensitively. In this study, Rhodamine B was determined using carbon paste electrodes modified with Fe3O4 and molecularly imprinted polyglycine (EPK-Fe3O4-MIP). The results of the Fe3O4 characterization using FTIR and SEM-EDS showed that there was a peak vibration of the Fe-O bond at wave number 586,36 cm-1, an average diameter of 32,776 nm with mass percent of Fe and O, respectively 61,13% and 38,87%. The electrodes modified with Fe3O4 and molecularly imprinted polyglycine gave the highest peak currents compared to those without modification. The optimum conditions for measurement were obtained using the SWV technique in 0,1 M phosphate buffer solution pH 7. EPK-Fe3O4-MIP had good repeatability and reproducibility with %RSD respectively 1,883% and 2,225%. The linear range of EPK- Fe3O4-MIP is 1 – 1.000 ?M with a measurement detection limit of 0,269 ?M. The measurement results also show that EPK-Fe3O4-MIP is quite selective towards Rhodamine B in the presence of interfering compounds commonly found in food. This electrode gave results that were not significantly different from sample measurements using a UV-Vis spectrophotometer.